Pemberdayaan masyarakat melalui e-commerce pada UMKM Kripik Tempe Kirana di Desa Lebak - Huda, Ahmad Munirul; Krismanto, M. Bayu; Dinillah, Nesa Fatha Dinillah; Suparwi, Sri (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Along with the development of the era, information technology is increasingly advanced and developing. The advancement of information technology has given rise to many innovations that can be utilized to support the improvement of the community's economy, such as e-commerce. E-commerce is an alternative means of facilitating online buying and selling transactions. Unfortunately, the community does not fully understand the use of this application, especially among rural communities. The lack of knowledge about e-commerce indicates this is a means of marketing MSME products. The community service program aims to help empower MSMEs in Lebak Village, one of which is tempeh chips MSMEs. This productive home business opens up job opportunities for the people of Lebak Village to improve the community's economic welfare. This community service implements the theory of Participatory Action Research (PAR) through four stages: planning, marking or implementation, observation, and reflection. The results of this empowerment show an increase in knowledge and interest in learning in the community to increase sales of MSMEs, especially tempeh chips, through e-commerce to buy and sell transactions to increase sales turnover.